2022
DOI: 10.1155/2022/1782955
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Nurse-Led Health Education on Self-Management Ability, Satisfaction, and Compliance of Elderly Patients with Chronic Obstructive Pulmonary Disease Based on Knowledge, Belief, and Practice Model

Abstract: Objective. Knowledge, belief, and behavior model (knowledge-attitude-practice (KAP)) is known as a cognitive model. Health education is important to the prognosis of patients, including chronic obstructive pulmonary disease (COPD) patients. However, the investigation regarding health education based on the KAP model is few. Thus, this work is aimed at analyzing the influence of nurse-led health education on self-management ability, satisfaction, and compliance of elderly patients with COPD based on knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The enhancement in illness perception paralleled with increased health services utilization in the intervention group, where a substantial proportion (69%) reported high utilization, as opposed to none in the control group. This aligns with findings from other studies indicating that interventions can significantly impact health behaviors and access to care, particularly in chronic disease management (47)(48)(49)(50).…”
Section: Discussionsupporting
confidence: 90%
“…The enhancement in illness perception paralleled with increased health services utilization in the intervention group, where a substantial proportion (69%) reported high utilization, as opposed to none in the control group. This aligns with findings from other studies indicating that interventions can significantly impact health behaviors and access to care, particularly in chronic disease management (47)(48)(49)(50).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, high-quality health education is essential for elderly patients with lung cancer. Some studies have found[ 20 ] that patients' satisfaction with traditional health education could be higher, mainly due to the lack of understanding of patients' needs and the lack of confirmation of patients' understanding of relevant knowledge. The IIFAR information nursing model effectively compensates for the shortcomings of traditional health education.…”
Section: Discussionmentioning
confidence: 99%
“…Education leads to improving the compliance of patients with COPD, changing their lifestyle and reducing the hospitalisation rate of these patients. 22 …”
Section: Discussionmentioning
confidence: 99%